Recognizing & engaging employees for dummies - Nelson, Bob 1956- (Hoboken, NJ John Wiley & Sons, Inc., 2015)
A guide to improving morale, productivity, and personal achievement at work. Nelson walks you step-by-step through incentives and mechanisms that must be in place for a recognition and engagement program to be effective in the long term.
Introduction -- Enhancing employee engagement through recognition -- The fundamentals of employee recognition -- Implementing recognition throughout the organization -- Creating and sustaining a culture of recognition -- Issues and challenges in recognizing and engaging employees -- The part of tens.
Includes index.
Keywords: Incentives in industry; Employee motivation